Preserving Cultural Heritage in Marriage: Exploring Meanings of Kebon Odeq Tradition in the Sasak Community of Central Lombok, Indonesia - Haerozi, Haerozi; Winengan, Winengan; Fakhri, Moh.; Sugitanata, Arif; Karimullah, Suud Sarim (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2023)
The convergence of customary norms with Islamic legal norms gives rise to a new legal entity, including philosophical meanings. However, it is often seen as problematic and potentially conflicting with Islamic legal principles. This article seeks to explore the symbolic meanings and reasons for the persistence of the kebon odeq in the marriage customs of the Sasak community in Pengadang Village, Central Lombok. Utilizing an anthropological approach with symbolic anthropology theory popularized by Victor Turner and conducting in-depth interviews with five key informants, this article reveals that within the kebon odeq, the Sasak community in Pengadang assigns significant symbolic meanings to various elements. The components of kebon odeq enhance a sense of unity and cultural values as a form of respect for ancestral customs. Symbolically, it emphasizes the correlation of its symbolic meaning with cultural values, marriage, and social aspects of society. In Islamic law, this tradition holds symbolic meanings related to the values of Islamic marriage, especially commitment and maintaining sustainability. The intersection of philosophical meanings between custom and Islamic law is a significant motivation for the extent to which kebon odeq is preserved and developed by the Sasak Muslim community.